Bacterial Community in Apis cerana and Heterotrigona itama Honey Using a Metabarcoding Approach - Nurjanah, Nurjanah; Raffiudin, Rika; Lestari, Yulin (Bogor Agricultural University, Indonesia, 2026)
Honey is a healthy, natural product with high nutritional value that is converted from sugar in nectar by bacteria in the honey stomach of the bees. Several beneficial bacteria in honey produce bioactive compounds, such as Lactobacillus in Apis mellifera honey, which synthesizes lactic acid, bacteriocins, and enzymes. Here, we employed the metabarcoding technique using the 16S rRNA gene to identify the bacterial community in honey from A. cerana and Heterotrigona itama collected in Sukabumi Regency, West Java, Indonesia. Genomic DNA from both honey samples was isolated using the ZymoBIOMICSTM DNA miniprep kit before sequencing with the Oxford Nanopore Technologies (ONT) platform. Our studies showed that the most dominant bacteria in the honey of A. cerana and H. itama were Paenibacillus glucanolyticus and Limosilactobacillus, respectively. In both types of honey, Gram-positive and Gram-negative bacteria were also detected, as well as lactic acid bacteria, including Acetilactobacillus jinshanensis and Limosilactobacillus. We also found Actinobacteria in A. cerana and H. itama honey. This genomic data showed that A. cerana honey has a higher bacterial diversity than H. itama. Our finding is the first genomic study of bacterial diversity found in the honey of A. cerana and H. itama that live sympatrically in a bee farm.